Neuroprotective effects of crude extract of Trigonella foenum graecum and Eurycoma longifolia in chronic cerebral hypoperfusion-induced neurodegeneration using rat model - Alruhaimi, Hulol Saleh D (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
Decreased cerebral blood supply to the brain can generate a condition of chronic cerebral hypoperfusion, which is one of the physiopathological mechanisms of neuronal degeneration and cognitive impairment in neurodegenerative disorders including Alzheimer's disease. Trigonella foenum graecum and Eurycoma longifolia Jack have been shown to have antioxidant and anti-inflammatory activities. Therefore, the aim of the current study was to evaluate the potential neuroprotective effect of ethanolic extract of Trigonella foenum graecum seeds (FS) and methanolic extract of Eurycoma longifolia roots (TA) on chronic cerebral hypoperfusion using rat animal model. Chronic cerebral hypoperfusion was induced by permanent bilateral ligation of the common carotid arteries in male Sprague–Dawley rats. The experimental groups were divided into four groups: a sham-operated group, a two-vessel occlusion (2VO) group, a 2VO group that was administered orally with the FS extract (100 mg/kg/day), and a 2VO group that was administered orally with the TA extract (100 mg/kg/day) from 3 days before the date of 2VO surgery and continued until the end of the 8th postoperative week. Spatial memory performance was assessed by the Morris water maze test. Serum malondialdehyde (MDA) content and superoxide dismutase (SOD), glutathione (GSH) activities, C-reactive protein (CRP) concentration were measured. The ultrastructural changes of the hippocampal area (CA1) were observed by transmission electron microscopic (TEM). Chronic cerebral hypoperfusion rats resulted in spatial memory impairments. This behavioural dysfunction was accompanied by decreasing SOD and GSH activities, increasing MDA content and increasing concentration of inflammatory marker (CRP) in serum. Similarly, ultrastructural neurodegenerative changes were observed in CA1 area of the 2VO group, which showed necrosis and apoptosis of pyramidal neurons, astrocytic degeneration with microgliosis, and thickening of endothelial basement membrane of hippocampal capillaries. Oral administration of FS extract significantly improved the memory impairment, enhanced antioxidant enzyme activities, decreased the content of MDA and the CRP levels to their normal levels as well as less ultrastructural changes in CA1 area of hippocampus. On the other hand, TA extract treatment showed a slight preservation of cognitive function, oxidative status and ultrastructural changes in CA1 region following chronic cerebral hypoperfusion. The potential activity offered by FS showed neuroprotective effect that may be beneficial in cerebrovascular type dementia. TA extract showed lesser neuroprotective effect. Further studies may be done to investigate the underlying mechanism.